MEKANISME PENGHITUNGAN, PELAPORAN, DAN PENYETORAN PAJAK PARKIR TAHUN 2017 MENURUT PERATURAN DAERAH PADA PT. PRADANA ENERGI GEMILANG - Yopy Ratna Dewi (POLITEKNIK LP3I JAKARTA, 2018)
AbstractPT. Pradana Energi Gemilang was established based on Deed No. 16 dated July 6, 2015 by Notary Indra Junardi, SE. SH. M.Kn in Jakarta. Until now, PT. Pradana Energi Gemilang is determined to remain a company that always prioritizes service quality and value through honesty, proactive attitude, friendliness and self-development and continuously strives for corrective actions in all fields. With the rapid growth and development especially in the Economy & Business sector, PT. Pradana Energi Gemilang is keen to participate as a businessman in it, as well as aiming to create jobs and create efficient and successful business for all of us, one of which is the business sector of parking management. Target of PT. Pradana Energi Gemilang is by creating security and comfort as a manifestation of customer satisfaction. By managing the overall operational professionally and regularly. Parking tax is a tax that has a positive contribution to improving regional financial capacity. This observation aims to find out whether PT. Pradana Energi Gemilang as a Parking Tax Taxpayer has implemented his tax obligations in accordance with the applicable tax regulations. Law Number 28 of 2009 and South Tangerang Mayor Regulation Number 64 of 2011 as the implementation rules.Keywords: Parking Tax, Regional Tax.